The Microbiome and Metabolome of Malignant Fungating Wounds: A Systematic Review of the Literature From 1995 to 2020. Issue 2 (March 2021) - Tilley, Charles P.; Fu, Mei R.; Qiu, Jeanna M.; Comfort, Christopher; Crocilla, Brooke L.; Li, Zujun; Axelrod, Deborah
Abstract : PURPOSE: Malignant fungating wounds (MFWs) afflict up to 14% of patients with advanced cancer. The bacterial community structures of MFW may influence the development and severity of wound symptoms. The purpose of this systematic review was to evaluate existing evidence regarding the relationship between microbiome and symptoms of MFWs. METHODS: A systematic review of the published literature from January 1995 to January 2020 was conducted. An established quality assessment tool was used to assess the quality of the included studies. SEARCH STRATEGY: We searched 4 major electronic databases and retrieved 724 articles; 7 met inclusion criteria. FINDINGS/CONCLUSIONS: Seven studies were included; the overall quality of the included 7 studies was ranked as adequate. Findings from the studies provided an incomplete characterization of the microbiome and metabolome of MFW; none included modern genomic technologies. Twenty different species of aerobes and 14 species of anaerobes were identified, with inconsistent identification of biofilms and multi-drug-resistant bacteria. Symptom occurrence increased with the number of bacteria species ( P = .0003) and the presence of at least 1 anaerobe ( P = .0006) in malignant wound beds. Cancer wound-derived odor was associated with dimethyl trisulfide and 4 fatty acid volatiles. Periwound and moisture-associated skin damage were associated with higher putrescine levels in exudates. IMPLICATIONS: Understanding the role of microbiota of MFW in developing or amplifying the severity of wound symptoms is the first step toward development of more precise and effective topical interventions. Abstract : Supplemental Digital Content is Available in the Text.The NCPD test for this article is available online only at the journal website, jwocnonline.com, and the test can be taken online at NursingCenter.com.